Predicting the Transmission of Covid-19 outbreak on Social Media Platform - Anil Kumar Jadon, Suresh Kumar (International Journal of Advanced Science and Technology, 2020)
On 30 January 2020, WHO declared the coronavirus disease (COVID-19) outbreak a Public Health Emergency of International Concern (PHEIC) and on 11 March 2020, WHO Director General characterized COVID-19 as a global pandemic. During this ongoing pandemic, Most of the countries are taking very hard decisions like travel bans, Social distancing enforcement, Self-quarantines, ban on public gathering and business closure. This has changed the way society used to live earlier worldwide. People are forced not to go out in public spaces, Conversations are happening more on online social media platform like Twitter. People are using these platforms to express their views, opinions and also reacting to government policies those are taken place in this COVID-19 crisis time. These platforms are also helpful for government to understand people reactions to the policies and measures taken by government to mitigate the social & economic risk and also the views, people are sharing. So there is need to have system that can present the public opinion regarding COVID-19 and predict the transmission of these views so that government can also consider the public point of views before making policies and implementing them on ground.Keywords: COVID-19, data analysis, polarity analysis, predictive modelling, Topic Modelling, LDA, PCA, Twitter, Artificial intelligence, Machine learning